Colours of humanity - U Tun Aung, Maulana Akbar Shah (2019)
Achievements, awards and recognition are often the driving factors in our lives. We race to conquer various accolades, often disregarding the finer things in life. In our pursuit for happiness, we often neglect the basic humanity and ethical values. In our quest for popularity, we sometimes hide our true inner self, projecting a cosmetic front. The talk will remind us that we are unique in our own ways despite the fundamental similarities and that we can be free to showcase our strengths without hiding behind a ‘common’ face. Come and engage with our speakers, listen to their stories and find your way to leading a life with basic humanity and ethical values. Get inspired!